Cuticle structure of Carpathian endemic species: Trachelipus trilobatus (Crustacea, Isopoda, Oniscidea) described with the scanning electron microscope - Diana CUPȘA; Traian-Octavian COSTEA; Alfred-Ștefan CICORT-LUCACIU; Severus-Daniel COVACIU-MARCOV; Sára FERENȚI (Studia Universitatis Babeș-Bolyai. Biologia)
The cuticle is the interface between an animal and its environment; thus, it has a special importance. In Arthropods, the cuticle is not uniform, having numerous formations, which is also the case of epigeic terrestrial isopods. Our study presents data on cuticle surface morphology, obtained with a scanning electron microscope, of an endemic terrestrial isopod species, Trachelipus trilobatus. Here we present SEM images of some external morphological features of this species, which were previously described only at the light microscope. Although T. trilobatus was frequently encountered in caves, the aspect of its cuticle is characteristic for an epigeic isopod, presenting numerous micro-scales, spines, and tricorn sensilla, which are considered hygroreceptors. This fact proves that originally T. trilobatus is an epigeic species, which secondarily adapted to karst areas with caves. Nevertheless, it regularly leaves the caves and the limestone cracks and emerges on the soil surface. Therefore, T. trilobatus is able to receive information about environmental humidity, especially on the soil surface, which, when unfavorable, causes the species retreat into caves or cracks. Climatic fluctuations from the glacial periods could direct T. trilobatus to this environment and way of life, modifying its morphology, but not its cuticle.